ANALYSIS OF THE EFFECT OF MACHINING VARIABLES ON SURFACE ROUGHNESS AND VIBRATION AMPLITUDE IN TURNING AISI 1045 STEEL USING THE TAGUCHI METHOD - Aji, Angga Asteriasti; Cesar Putra, Fachrizal; Badia, Bahdin Ahad; Idris Putra, Muhammad; Sahputra, Wahyu Puji; Darwis, Mardis; Hasudungan Simanjuntak, Raja Agung (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The development of the manufacturing industry is growing very rapidly so that the products of the manufacturing industry must have high quality, especially machining products such as turning products. This research investigates the effect of turning parameters, namely feed and spindle rotation on surface roughness and vibration amplitude of turning AISI 1045 steel using carbide tools. Surface roughness measurements were taken using an OLS4100 Microscope and vibration amplitude was measured using a Vibxpert II. From the results of the analysis conducted, the feed factor is the most significant factor on the results of surface roughness and vibration amplitude. The most optimal machining parameters for surface roughness are feed 0.1 mm/put (lvl 1), spindle speed 400 rpm (lvl4) with a surface roughness value of 4.757 µm. The most optimal machining parameters for vibration amplitude are feed 0.1 mm/put (lvl 1) and spindle speed 100 rpm (lvl 1) with a vibration amplitude value of 0.11 m/s.